Effect of Opuntia ficus-indica Mucilage Edible Coating in Combination with Ascorbic Acid, on Strawberry Fruit Quality during Cold Storage. (30th May 2021) - Liguori, Giorgia; Gaglio, Raimondo; Settanni, Luca; Inglese, Paolo; D'Anna, Fabio; Miceli, Alessandro
Abstract : Strawberry fruit is a nonclimacteric fruit and is one of the most consumed berries in the world. It is characterized by high levels of vitamin C, folate, vitamin E, β -carotene, and phenolic constituents as well asanthocyanins that are strictly related to health benefits. Strawberries are highly perishable fruit with a very short postharvest life due to their susceptibility to mechanical injury, rapid texture softening, physiological disorders, and infection caused by several pathogens (yeast and mold) that can rapidly reduce fruit quality. The aim of the present study was to evaluate the effect of the application of Opuntia ficus-indica mucilage in combination with ascorbic acid, as edible coating, on quality, sensorial parameters, and microbiological characteristics of strawberry fruit during cold storage at 4 ± 0.5°C and 85% RH. Strawberries were characterized by a linear increase of weight loss during the storage at 4°C that was significantly higher (+11.3% on average) in the uncoated strawberries. The coating affected the ascorbic acid content of the strawberries that increased by 36.0% in coated strawberries; total soluble solid content and color of the strawberries were only affected by storage. Visual quality and sensorial analysis recorded higher scores in the coated samples at the end of the cold storage period. Furthermore, the mucilage coating did not negatively affect the natural taste of strawberries. The application of O. ficus-indica gel-based edible coating in combination with ascorbic acid, although not able to inhibit the microbial growth, limited significantly their development in coated strawberry fruits. Our results suggest that Opuntia mucilage plus 5% ascorbic acid could be a useful biochemical way of maintaining strawberry fruit quality and extending their postharvest life.